2017
DOI: 10.1128/aac.02656-16
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prophylaxis Is Associated with Subsequent Resistant Infections in Children with an Initial Extended-Spectrum-Cephalosporin-Resistant Enterobacteriaceae Infection

Abstract: The objective of this study was to assess the association between previous antibiotic use, particularly long-term prophylaxis, and the occurrence of subsequent resistant infections in children with index infections due to extended-spectrumcephalosporin-resistant Enterobacteriaceae. We also investigated the concordance of the index and subsequent isolates. Extended-spectrum-cephalosporin-resistant Escherichia coli and Klebsiella spp. isolated from normally sterile sites of patients aged Ͻ22 years were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Clearly, causes other than NICU practice were responsible for the fact that ESBL-producing E. coli has emerged as the main pathogen for EOS in our NICU. There are several studies that have demonstrated the relationship between the antibiotic chosen for IAP and resistant E. coli infections in neonates 21,22. Colonization of resistant bacteria in pregnant women during hospitalization may be another reason.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, causes other than NICU practice were responsible for the fact that ESBL-producing E. coli has emerged as the main pathogen for EOS in our NICU. There are several studies that have demonstrated the relationship between the antibiotic chosen for IAP and resistant E. coli infections in neonates 21,22. Colonization of resistant bacteria in pregnant women during hospitalization may be another reason.…”
Section: Discussionmentioning
confidence: 99%
“…Koh et al [27] suggest that prolonged courses of antibiotic administration in PE may reduce septic complications, which is in contrast to the findings of Ishibashi et al [28] on patients undergoing surgery for rectal cancer; the authors did not observe a significant reduction in SSI incidence among patients receiving a single dose of postoperative antibiotics vs. multiple-dose antibiotics. Other authors argue that prolonged courses of antibiotic prophylaxis may cause the risk of increasing microbial resistance infections [29,30]. However, in a large retrospective cohort study by Cohen et al [31], among 689 patients with post-operative infections, there was no association between antibiotic prophylaxis and post-operative antibiotic-resistant infections.…”
Section: Discussionmentioning
confidence: 98%
“…For each resistant isolate, 3 consecutive E. coli isolates that were susceptible to the aforementioned agents, referred to here as extended-spectrum cephalosporin-susceptible (ESC-S) isolates, were collected without respect to any patient or microbiological characteristics beyond temporal proximity to the ESC-R isolates and prior enrollment in the study (patients could only contribute 1 ESC-S isolate). Demographic and clinical data were collected from the medical records; methods for categorizing underlying medical conditions, capturing antibiotic exposure, and characterizing the clinical significance of urine isolates (likely urinary tract infection vs not) were described previously [21,22]. The institutional review board at each hospital approved the study protocol.…”
Section: Patients and Isolatesmentioning
confidence: 99%